Health Expenditure Targeting, Financial Protection and Maternal Mortality in Sub-Saharan Africa - Peter Igbaudumhe Sede (Faculty of Economics, Universitas Sriwijaya, 2020)
The slow reduction in maternal mortality rate in Sub-Saharan Africa is a serious cause for policy concern. This has not only retained the sub region in the web of leading region in high rate of reproductive health challenges but spells signals of poverty and low economic growth. The study therefore, examined the efficacy of health expenditure targeting and financial protection in reducing maternal mortality in 44 Sub-Saharan Africa countries. The study adopts fixed effect panel data modelling technique. Results show that financial protection is correctly signed but not statistically significant while relative health expenditure targeting is both correctly signed and statistically significant in reducing maternal mortality. Recommendation is that health expenditure should generally be increased so as to increase the slope of decrease in maternal mortality rate in Sub-Saharan Africa and health expenditure should be more targeted against GDP as common denominator.